KEARIFAN LOKAL MASYARAKAT SAKAI DALAM MELESTARIKAN HUTAN DAN SUNGAI DI KECAMATAN MANDAU - Henni Elyati; Zulfan Saam; Yusni Ikhwan Siregar (Program Pascasarjana Universitas Riau, 2015)
ABSTRACTThis research was conducted in February-June 2015 in the village of Kesumbo Ampai, District of Mandau, Bengkalis. The research was aimed to identify the forms of Sakai tribe's local wisdom toward forest sustainability and the local wisdom itself and analyze its influence toward the river sustainability concept. The method used in this research was qualitative method that was designed to provide a detailed overview on specific individuals or groups in a particular circumstance and symptom. In order to understand the forms of Sakai tribe's local wisdom, the researcher conducted in-depth interviews with the Sakai community leaders, village heads and the Head of Bengkalis' Culture and Tourism Department. The result showed that Sakai's local wisdom can preserve forests and rivers in their vicinity area. One of the methods used to preserve the forest ecology is by applying a strict land zonification. In regards to the land clearing, the Sakai people keeps using a simple technology until now. For the seeds planting as well, the Sakai people does not work the land and the plants are maintained using organic fertilizers. The simplicity of the technology is a symbol of environmental wisdom. For hunting or fishing at the river, the Sakai people uses traditional equipment that are environmentally friendly so that the river area can be preserved.